The Effectiveness of Setu Babakan Cultural Village as a Betawi Language Preservation Model: An Anthropolinguistic Study - Anjani, Sara Dwi; Siregar, Iskandarsyah; Susanto, Arju (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2024)
This research analyzes the Setu Babakan Cultural Village as a preservation of the Betawi language. The research aims to explore the use of the Betawi language in the Setu Babakan Cultural Village and the role of the Setu Babakan Cultural Village in preserving the Betawi language. The method used combines qualitative and quantitative methods, with data collection through interviews and questionnaires and data analysis through descriptive analysis. This research uses anthropolinguistic theory, a science combining anthropology and linguistics. The research results show that the Setu Babakan community is very committed to preserving the Betawi language and actively maintains the use of the Betawi language in daily communication. The research conclusions show that efforts to protect the Betawi language in this cultural village have had a significant positive impact. We have created an environment that supports preserving the Betawi language and culture through strategies including community programs, education, and conservation efforts. Therefore, this research provides a better understanding of language preservation efforts, especially in the context of regional languages such as Betawi in the Setu Babakan Cultural Village.